DISTANCE E-LEARNING AND ITS IMPACT ON UNIVERSITY EDUCATION OUTCOMES FROM THE STUDENTS’ POINT OF VIEW - AL-Momani, Mohammad Omar; AL-Momani, Manal Abdul Karim; Hamadat, Mohammad Hasan; Murtada, Mariam Ayed (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2024)
This pioneering study aimed to unravel the nuanced impact of distance e-learning on the outcomes of university education, specifically gauging the perspectives of Jordanian university students while considering the variables of gender and academic year. Employing a multifaceted methodology, the research adopted a descriptive approach augmented by an electronically distributed questionnaire, meticulously tailored to assess students' perceptions. A diverse cohort of 1,000 male and female students, selected through a rigorous random sampling method, participated in the study during the inaugural semester of the 2023/2024 academic year. Results unveiled a strikingly high perceived impact of distance e-learning on university education outcomes, with an average score of 3.70 and a standard deviation of 0.62, indicative of a robust consensus among students. Intriguingly, while concerns regarding the negatives of e-learning dominated discourse, the positives of distance education also garnered substantial recognition, albeit ranking slightly lower. Furthermore, the field of outcomes of distance e-learning emerged with a moderate degree of impact, underscoring the multifaceted nature of its influence. Notably, statistical analysis revealed no discernible differences in perceptions across gender or academic year cohorts, suggesting a uniform perspective on the efficacy of distance e-learning among Jordanian university students. These findings not only enrich scholarly discourse but also offer valuable insights for educational policymakers and practitioners seeking to optimize the integration of e-learning modalities in university settings.